Avaliação da doença hepática gordurosa não alcoólica em mulheres na pós-menopausa - Bruno, Anderson de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
To evaluate the prevalence and the risk factors of the nonalcoholic fatty liver disease (NAFLD) in Brazilian postmenopausal women. In this cross-sectional study, 188 women (age ≥45 years and amenorrhea ≥ 12 months) followed the Belo Horizonte Specialty Clinic from January 2011 to August 2012, were included. Exclusion criteria were: liver disease (hepatitis B and C, cholestatic disease, liver insufficiency and tumor), use of drugs that affect the liver metabolism; alcoholics; HIV or cancer history; and morbid obesity. NAFLD was diagnosed by abdominal ultrasound. Clinic, anthropometric (body mass index, BMI and waist circumference, WC) and biochemical variables were measured. The student t-test, Gamma distribution, Chisquare test and logistic regression (odds ratio-OR) were used for the statistic analysis. Of the 188 women, 38.8% had NAFLD. In 45.2% (33/73) of those patients, the steatosis was considered mild, in 42.5% (31/73) moderate and severe in 12.3% (9/73). Blood pressure, WC, BMI, LDL, triglycerides, glucose, insulin, alanine aminotransferase (AST) were significantly higher in NAFLD patients when compared without NAFLD women (control group) (p <0.05). The HOMA-IR average values showed insulin resistance only in the NAFLD group (6.1±4.6 vs 2.4±1.4 in control, p<0.05). The metabolic syndrome (MetS) was detected in 93.1% of women with NAFLD, and in 46.1% of control (p<0.05). In multivariate analysis, adjusted for for age and weight, the variables considered at risk for the development of NAFLD were: high WC (OR 1.07, 95% CI 1.01-1.13); plasma insulin (OR 1.12, 95% CI 1.05-1.19), HOMA-IR (OR 3.81, 95% CI 2.01-7.13), and presence of MetS (OR 8.68, 95% CI 3.3- 24.1). Nonalcoholic fatty liver disease showed high prevalence among Brazilian postmenopausal women. The presence of metabolic syndrome, abdominal obesity and insulin resistance were indicators of risk for the development of hepatic steatosis

Avaliar a ocorrência e os fatores de risco da doença hepática gordurosa não alcoólica (DHGNA) em mulheres na pós-menopausa. Estudo clínico, transversal, envolvendo 188 mulheres na pós-menopausa (idade ≥ 45 anos e amenorréia ≥ 12 meses) acompanhadas em Ambulatório de Especialidades de Belo Horizonte de janeiro de 2011 a agosto de 2012. Critérios de não inclusão foram: doença hepática (hepatites B e C, doença colestática, insuficiência hepática e tumor); uso de drogas que afetam o metabolismo hepático; etilistas; antecedente de HIV ou câncer; e obesidade mórbida. A DHGNA foi diagnosticada por meio da ultrassonografia abdominal. Foram realizadas avaliações clínicas, antropométricas (índice de massa corpórea, IMC e circunferência da cintura, CC) e bioquímicas. Para análise estatística foram empregados os testes de t-student, distribuição Gama, Qui-Quadrado, regressão logística (odds ratio- OR). Das pacientes incluídas no presente estudo, 38,8% (73/188) apresentaram diagnóstico de esteatose hepática, sendo considerada leve em 45,2% (33/73) das pacientes, moderada em 42,5% (31/73) e, grave em 12,3% (9/73). As mulheres com DHGNA apresentaram valores pressóricos e CC elevados, e o IMC compatível com obesidade (31.5±4.5kg/m2) (p<0.05). Assim como, os valores médios de LDL, triglicerídeos, glicemia, insulina, ALT/TGP foram significativamente superiores as mulheres sem esteatose (controle) (p<0,05). Os valores médios do HOMA-IR indicaram resistência à insulina apenas no grupo com a DHGNA (6.1±4.6 vs 2.4±1.4 no controle; p<0.05). Encontrou-se diferença quanto à presença de síndrome metabólica (SM), detectada em 93.1% das mulheres com DHGNA e em 46.1% no controle (p<0.05). Em análise multivariada, ajustada para idade e peso, as variáveis consideradas de risco para o desenvolvimento da DHGNA foram: circunferência da cintura elevada (OR 1.07, IC 95% 1.01-1.13); insulinemia ...
Keywords: Pós-menopausa; Figado - Doenças - Diagnostico; Mulheres - Doenças; Obesidade; Resistência à insulina; Síndrome metabólica; Liver Diseases Diagnosis